Influence of blanching and frozen storage on quality characteristics of vegetable soybean (Glycine max) - THAKUR, ABHAY KUMAR; PAN, RABI SHANKAR; SINGH, INDU SHEKHAR; SHAMBHU, VIDYA BHUSHAN (The Indian Journal of Agricultural Sciences, 2022)
Effect of blanching on freezing and quality attributes during frozen storage of vegetable soybean [Glycine max (L.) Merrill] was investigated during 2015–16 at ICAR-RCER, RC Ranchi. Seeds were blanched for 5 and 10 min in boiling water, steam and microwave. Freezing was carried out at -20oC and stored in frozen condition (-18oC) for 12 months. Quality attributes such as drip loss, ascorbic acid, chlorophyll, hardness, colour, microbiological status and sensory trait were examined. Green seeds (58.3%) were recovered from harvested vegetable soybean pod, in which 54.8% were good seeds and 3.5% were physically damaged. Drip loss of frozen samples was between 3.68% and 5.54% during the storage period. A loss of 35.7% was found in ascorbic acid after blanching that further reduced to 71.9% after 12 months of frozen storage. Chlorophyll reduced to 21.9% due to blanching and freezing that further decreased to 42.4% at the end of storage. Blanching treatments did not show significant variation in hardness while losses of hardness were significant during storage. Colour retention was better in samples blanched in boiling water or steam. Bacterial and fungal count at the end of 12 months frozen storage suggested that samples were microbiologically safe to consume. Sensory examination revealed that 10 min blanching either in boiling water or in steam was more acceptable vis-à-vis samples blanched in microwave.